2016
DOI: 10.3389/fmicb.2016.01671
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Susceptibility of Autochthonous Aquatic Vibrio cholerae in Haiti

Abstract: We investigated the antimicrobial susceptibility of 50 environmental isolates of Vibrio cholerae non-O1/non-O139 collected in surface waters in Haiti in July 2012, during an active cholera outbreak. A panel of 16 antibiotics was tested on the isolates using the disk diffusion method and PCR detection of seven resistance-associated genes (strA/B, sul1/2, ermA/B, and mefA). All isolates were susceptible to amoxicillin-clavulanic acid, cefotaxime, imipenem, ciprofloxacin, norfloxacin, amikacin, and gentamicin. Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 39 publications
3
14
2
Order By: Relevance
“…The observation of resistance amongst the V. cholerae to these antibiotic group is a potential determinant of epidemiological relevance especially when considering future strategies for management of cholera cases. Similar to the above observation is the reports from other clinical/environmental studies in the Asian continent (China, Mumbai, North India) (outside Africa) and other regions (Haiti) which have also reported similar occurrence of resistance to the cephalosporin group of antibiotics [ 59 , 76 , 77 , 78 ]. Their studies accessed water and stool samples and observed both O1/O139 and non-O1/nonO139 V. cholerae strains of diverse virulent and multiple antibiotic resistant determinants.…”
Section: Discussionsupporting
confidence: 90%
“…The observation of resistance amongst the V. cholerae to these antibiotic group is a potential determinant of epidemiological relevance especially when considering future strategies for management of cholera cases. Similar to the above observation is the reports from other clinical/environmental studies in the Asian continent (China, Mumbai, North India) (outside Africa) and other regions (Haiti) which have also reported similar occurrence of resistance to the cephalosporin group of antibiotics [ 59 , 76 , 77 , 78 ]. Their studies accessed water and stool samples and observed both O1/O139 and non-O1/nonO139 V. cholerae strains of diverse virulent and multiple antibiotic resistant determinants.…”
Section: Discussionsupporting
confidence: 90%
“…A recent study found no ermA gene and 90% of V. cholerae isolates harboured the ermB gene. 57 The present study found that isolates showed no amplification for the ermA and ermB genes. So, erythromycin is a good choice for treating cholera infections.…”
contrasting
confidence: 41%
“…For doxycycline and erythromycin, no breakpoint were available, based on the distribution of the diameter of inhibition (Figures 4A,B ), only one population could be observed. All the strains were considered as susceptible (Baron et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%